Identification dynamic behaviour of disc brake based on finite element model updating approach - Mohd Sahril, Mohd Fouzi; M. S. M., Sani; M. F. R., Ishak (IOP Publishing, 2019)
Braking system is an essential mechanism that designed to provide a good handling in order to slow down or to stop a vehicle depends on situation and driver's capability. In order to slow down or to stop the vehicle, brake pad will be pushed and make contact with the disc/rotor to form the friction. Resultant from braking event, it will produce vibration on disc/rotor structure. Thus, this study presents numerical prediction approach to identify the dynamic behaviour of disc brake structure using normal mode analysis in FEA software. Since the result of FEA is a prediction, the fidelity of FE model might be questioned. Therefore, measured data from EMA used to validate the predicted result of FEA through correlation process. As FE model used in this study made from assumption and simplification apart of real structure, it drive to discrepancy between FEA result and EMA data during correlation process. Hence, FE model updating approach implemented in order to reduce the discrepancy and increase the trustworthiness of FE model and it is become the main goal in the present study. The updating process has successfully reduced the discrepancy between FEA and EMA from 9.00 % of error to 4.05 % of error from its original value. As conclusion, the use of model updating process is important in preparing a reliable FE model of test structure no matters how simple or complex it is before being used for further analysis.